Persistent effects of high frequency repetitive TMS on the coupling between motor areas in the human. - Oliviero, A; Strens, L; Di Lazzaro, V; Tonali, P; Brown, P (2003)
Repetitive transcranial magnetic stimulation (rTMS) shows promise as a treatment for various movement and psychiatric disorders. How rTMS may have persistent effects on cortical function remains unclear. We hypothesised that it may act by modulating cortico-cortical connectivity. To this end we assessed cortico-cortical coherence before and after high frequency rTMS of the motor cortex. Sixteen healthy subjects received a single train (5 Hz, active motor threshold, 50 stimuli) of rTMS to the left motor hand area. Spectral power and coherence estimates were calculated between different EEG signals at rest and while muscles of the distal upper limb were tonically contracted. Repetitive TMS over the left motor hand area caused a significant decrease in the intrahemispheric EEG-EEG coherence between motor and premotor cortex in the 10.7-13.6 Hz (upper alpha band) lasting a few minutes after stimulation. There was no significant change in interhemispheric EEG-EEG coherence between motor areas. Thus, high frequency rTMS of the motor cortex decreases ipsilateral cortico-cortical intrahemispheric in the upper alpha band.